Sustainable governance in relation to the financial aspect in managing coastal areas: Malaysian experience - Asmawi, M. Zainora; Mahamod, Lukman Hakim; Mohamed, Mohd Zin; Paiman, Tuminah (Malaysian Institute of Planners, 2014)
Managing natural resources sustainably is essential in this contemporary era of land use planning system. This includes managing and planning the invaluable of coastal areas. In this regards, coastal management programmes have been regarded as a key approach in delivering the coastal strategies and objectives towards achieving a sustainable coastal development worldwide. This is supported by the good governance to ensure that the implementation of coastal development is successful. As such, this paper suggests that the aspect of good governance as one essential element of coastal management that can and should make a substantial contribution to planning and managing coastal land uses in Malaysia. It has many positive implications to the environmental, social and economic sectors. The experience of Lembaga Urus Air Selangor (LUAS) in managing the coastal areas via the implementation of good governance indicates the requirement of good governance in ensuring a successful coastal management. In addition, financial element has become a significant attribute in implementing coastal management initiatives. This study offers input in planning literatures by addressing the integration of coastal management, good local governance, land use planning and financial elements which are very relevant with today‘s current global changes on environment as a whole.